Hanbury Brown-Twiss effect without two-photon interference in photon counting regime - Bai, Bin (Sci Rep, 2017)
From quantum point of view, Hanbury Brown-Twiss effect is a result of constructive-destructive two-photon interference. There should be no Hanbury Brown-Twiss effect if there was no two-photon interference. In this paper, we observed Hanbury Brown- Twiss effect in a specially designed experiment, in which two-photon interference is impossible by keeping only one two-photon probability amplitude in the experimental scheme. However, our experimental results can still be interpreted by Glauber’s quantum optical coherence theory. The researches in our paper are helpful to understand the physics of the second-order coherence of light, especially the physics of Hanbury Brown-Twiss effect.